Odpowiedzi

2009-12-09T22:42:28+01:00
Nie wyświetla mi się potęga przy pierwszym x wielomianu W wiec przyjmę, że to 4

H(x)=W(x) + G(x) =x⁵+2x³+4x² +x³-2x² =x⁴+3x³+2x²

P(x)=W(x)-G(x) =x⁵+2x³+4x² -x³+2x²=x⁴+x³ +6x²

F(x)=2W(x) =2*(x⁵+2x³+4x²) =2x⁴+4x³+8x²
Najlepsza Odpowiedź!
2009-12-09T22:48:09+01:00
W(x)=x⁵+2x³+4x² , G(x)=x³-2x²
1) H(x)=W(x) + G(x)
2) P(x)=W(x)-G(x)
3) F(x)=2W(x)

1) H(x)=W(x) + G(x) = x⁵+2x³+4x² +x³-2x² =
= x⁵ +3x³ +2x²

2) P(x)=W(x)-G(x) = x⁵+2x³+4x² -(x³-2x² )=
= x⁵+2x³+4x² -x³+2x² =
= x⁵+x³ +6x²

3)3) F(x)=2W(x) = 2*(x⁵+2x³+4x² ) =
= 2x⁵ +4x³ + 8x²
2009-12-09T22:53:29+01:00
W(x) = x^5 =2x^3 +4x^2; G(x) = x^3 - 2x^2

H(x) = W(x) + G(x) = x^5 + 3x^3 + 2x^2
P(x) = W(x) -G(x) = x^5 + x^3 + 6x^2
F(x) = 2 W(x) = 2x^5 + 4x^3 + 8 x^2